2018
DOI: 10.1037/hum0000099
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting verbal hallucinations: The relevance of Gadamer’s philosophical hermeneutics.

Abstract: This article seeks to defend the thesis that Auditory Verbal Hallucinations (AVHs) can be interpretable and meaningful phenomena. By meaningful, I mean to argue that AVHs can be motivated events-even if they are experienced as alien and uncontrollable-and, as such, they are expressions the meanings of which can be seen as determined in a manner comparable with dialogical speech. In working toward a hermeneutic of AVHs, I will begin by reviewing pertinent literature that justifies the claim that we can view cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Thus, the questioning of diagnostic categories related to AVH ( Woods, 2013 ) has led to research bringing a more detailed understanding of the similarities and differences between the phenomenon and the condition of psychosis ( Baumeister et al, 2017 ; Braun, Evrard and Génot, 2020 ; Moskowitz, Mosquera and Longden, 2017 ; Sommer and Van der Spek, 2016 ). Similarly, further study has shown how the phenomenon may be preferentially associated with psychosocial characteristics ( Longden, 2017 ), personal variables such as self-esteem and self-consciousness ( Fannon et al, 2009 ; Naudin et al, 2000 ), shame ( Woods, 2017 ), and the disruption of the relationship between an individual’s outward speech and their inner thoughts ( Brar, 2018 ). Finally, original studies have highlighted the role and place of gender in AVH ( McCarthy-Jones et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the questioning of diagnostic categories related to AVH ( Woods, 2013 ) has led to research bringing a more detailed understanding of the similarities and differences between the phenomenon and the condition of psychosis ( Baumeister et al, 2017 ; Braun, Evrard and Génot, 2020 ; Moskowitz, Mosquera and Longden, 2017 ; Sommer and Van der Spek, 2016 ). Similarly, further study has shown how the phenomenon may be preferentially associated with psychosocial characteristics ( Longden, 2017 ), personal variables such as self-esteem and self-consciousness ( Fannon et al, 2009 ; Naudin et al, 2000 ), shame ( Woods, 2017 ), and the disruption of the relationship between an individual’s outward speech and their inner thoughts ( Brar, 2018 ). Finally, original studies have highlighted the role and place of gender in AVH ( McCarthy-Jones et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%